Interpretations of the tower of Babel narrative in the African context - Rathbone, Mark (Acta theologica, 2014)
Biblical scholarship from the African context provides possible new and creative perspectives for the interpretation of the Tower of Babel narrative because of uniquely African questions that structure the interpretative process. These unique questions relate to the cultures of African people, the injustice of colonialism, apartheid and so forth. The problem is that some of these new perspectives are influenced by rationalism that may result in reductionist interpretations of the Tower of Babel narrative. This is clear in the African cultural hermeneutics of Solomon Avotri and Black African hermeneutics of emeritus arch-bishop Desmond Tutu. The contemporary move among some biblical scholars from the African context that focus on the interaction between scholarly and non-scholarly interpreters of the Bible is an attempt to address the problems associated with rationalism. The art of Azaria Mbatha will be used to illustrate the potential of this contemporary move.